Cobalt‐catalyzed Aerobic Oxidation of Eugenol to Vanillin and Vanillic Acid. Issue 3 (26th January 2016) - Mao, Haifang; Wang, Lizhi; Zhao, Feifei; Wu, Jianxin; Huo, Haohua; Yu, Jun
Abstract: A novel, simple, one‐step method of synthesizing vanillin and vanillic acid from eugenol has been developed. The method uses ligand‐ and additive‐free Co(OAc)2 ⋅ 4H2 O as catalyst and molecular oxygen as oxidant to achieve catalytic process without isomerizing eugenol. Extensive screening efforts were used to optimize eugenol to obtain vanillin and vanillic acid. Under optimal conditions, the reaction provided vanillin and vanillic acid with 68.5 % and 15.2 % yields, respectively. Apart from the desired products, coniferyl alcohol 9‐methyl ether and 4‐hydroxy‐3‐methoxycinnamaldehyde as two intermediates were also detected in the reaction process. Level changes of all compounds over time were presented in the reaction. The reaction pathway from eugenol to vanillic acid was validated by conducting several control experiments. Furthermore, a possible reaction mechanism dominated by a circular redox reaction from Co(III) and Co(II) species was proposed. This method offers a potentially practical alternative for manufacturing vanillin and vanillic acid efficiently. Abstract : Vanillin and vanillic acid are two types of popular flavoring materials used worldwide. In this study, Co(OAc)2 without ligand and additive was used as the reaction catalyst, and its catalytic performance for aerobic oxidation of eugenol to vanillin and vanillic acid was investigated for the first time.